Power generation expansion planning with high penetration of geothermal energy – Potential, prospects and policy - Muhammad Amir Raza; Mahmoud Ahmad Al-Khasawneh; Yahya Z. Alharthi; Muhammad Faheem; Raza Haider; Laveet Kumar (Environmental and Sustainability Indicators)
Climate is changing due to greater carbon emissions with observable effects like severe weather events, shifts in precipitation patterns, rising sea levels, and warming oceans. Hence power generation expansion planning with high penetration of geothermal energy is proposed in Pakistan for sustainable climate environment. Pakistan is blessed with 100 GW of geothermal capacity and it is exploited using the Low Emissions Analysis platform (LEAP) software for the study period 2024 to 2060 by taking the base year 2023. The results revealed that for the year 2024 geothermal energy will be produced around 33.12 TWh which then increased to 58.07 TWh until 2027, 108.15 TWh units until 2030 to 364.56 TWh units until 2040, 787.91 TWh units until 2050 and 1599.99 TWh units until 2060. Further, the investment cost is forecasted that 1.07 US billion $ until 2024 which then enhanced to 2.13 US billion $ until 2027, 3.41 US billion $ until 2030, 9.83 US billion $ until 2040, 24.42 US billion $ until 2050 and 55.34 US billion $ until 2060. The forecasted capacity of geothermal is capable of reducing 30% carbon emissions until 2030 and further it reduces 50% and 100% carbon emissions until 2030 and 2040. This study provides zero-emission solutions, climate risk management, equity, and justice in the climate action goals worldwide.